The Effects of Catholic and Protestant Schools: A Meta-Analysis - Jeynes, William H. (Catholic Education: A Journal of Inquiry and Practice, 2008)
A meta-analysis was undertaken including 41 studies to determine the influence of Catholic and Protestant schools. The analysis examined studies undertaken at both the elementary and secondary school level. The results indicate that both Catholic and Protestant school students do better than their counterparts in public schools. In addition, Protestant school students excelled more than their Catholic counterparts on most standardized tests, but Catholic school students did better than their Protestant school counterparts on non-standardized measures. The significance of these results is discussed.